RVA levels in the small intestine (A) and large intestine (B); RVA shedding (rectal swabs) (C). - Sergei A. Raev (15350287) (2025)
Six-day-old germ-free pigs were orally inoculated with 1 × 106 FFU of rotavirus. Swabs were collected at designated time points. For the small and large intestine contents pigs were euthanized at the post-inoculation times indicated and contents were collected. RVA quantification was performed with cell culture immunofluorescence (CCIF). Significant differences (*p < 0.05, ** p < 0.01, p < 0.001) are indicated as calculated by using two-way ANOVA with repeated measures and the Tukey-Kramer test for multiple comparisons. (TIF)